If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(7 + -1y) + -3(y + 4) + -4 = 4(y + -3) + 7 (7 * 5 + -1y * 5) + -3(y + 4) + -4 = 4(y + -3) + 7 (35 + -5y) + -3(y + 4) + -4 = 4(y + -3) + 7 Reorder the terms: 35 + -5y + -3(4 + y) + -4 = 4(y + -3) + 7 35 + -5y + (4 * -3 + y * -3) + -4 = 4(y + -3) + 7 35 + -5y + (-12 + -3y) + -4 = 4(y + -3) + 7 Reorder the terms: 35 + -12 + -4 + -5y + -3y = 4(y + -3) + 7 Combine like terms: 35 + -12 = 23 23 + -4 + -5y + -3y = 4(y + -3) + 7 Combine like terms: 23 + -4 = 19 19 + -5y + -3y = 4(y + -3) + 7 Combine like terms: -5y + -3y = -8y 19 + -8y = 4(y + -3) + 7 Reorder the terms: 19 + -8y = 4(-3 + y) + 7 19 + -8y = (-3 * 4 + y * 4) + 7 19 + -8y = (-12 + 4y) + 7 Reorder the terms: 19 + -8y = -12 + 7 + 4y Combine like terms: -12 + 7 = -5 19 + -8y = -5 + 4y Solving 19 + -8y = -5 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 19 + -8y + -4y = -5 + 4y + -4y Combine like terms: -8y + -4y = -12y 19 + -12y = -5 + 4y + -4y Combine like terms: 4y + -4y = 0 19 + -12y = -5 + 0 19 + -12y = -5 Add '-19' to each side of the equation. 19 + -19 + -12y = -5 + -19 Combine like terms: 19 + -19 = 0 0 + -12y = -5 + -19 -12y = -5 + -19 Combine like terms: -5 + -19 = -24 -12y = -24 Divide each side by '-12'. y = 2 Simplifying y = 2
| 3N=54 | | 6.4y-9=5.4y-9 | | 8*25= | | 6.5x-5=5.5x | | 5p+3=4p+9 | | 9x(x-5)=0 | | -30+3x=6 | | 15y^2-15t-30=0 | | (0.1x^8)(0.3x^3)= | | 4x-(-10)=-22 | | 4x+9=3x-12 | | 5x-(-10)=-35 | | z^2+12z+5=0 | | -3x^2+4x+2=0 | | 8R^2-24R=O | | lnx=7 | | 7x-9y=5 | | -30x^2+9x+12=0 | | 7u+4v=-14 | | V=cqt | | X+3.1=6.8 | | 3x^2+12x+13=0 | | -(8y+2)-(-7Y-3)=1 | | 7x^2-8=-3 | | 5(3x+2)-4= | | -32-12x=2x+8 | | 3x^2-14x-56=0 | | 3(n-5)=8+4n | | 0=x^2-5x+14 | | 0=x^2-x+5 | | 50*2+150*2= | | x(2+5x)=0 |